Offenders' perceptions of the choices they had and the choices they made - Gathings, M.J. (2007)
"African Americans are overrepresented among arrests, defendants, and convictions despite no significant differences in self-reports of criminal offending between African Americans and Whites. This research examines the differences in family and educational experiences among fifteen men who live in North Carolina. Retrospective interviews were conducted face-to-face with adult men who attended N.C. public schools and had been previously apprehended for a criminal law violation. Patterns of socialization and class- and race-based differences are analyzed. Results indicate no substantial differences in school experiences between African Americans and Whites in the sample. However, findings suggest race is salient for criminal justice outcomes."--Abstract from author supplied metadata